The scientific discourse circulated during a national-populist commemoration: Dannunzian Fiume and the 'Italo-cosmopolitan' field of history. Issue 1 (February 2023) - Lamour, Christian
Abstract: In today's Europe, commemorations can be times at which to affirm international reconciliation, based notably on the knowledge produced by historians who are becoming progressively cosmopolitan. However, commemorations are also used by national-populist political parties for electoral purposes and can lead to tensions with neighbouring states. This was the case in Trieste in September 2019, when the city council executive (controlled by a right-wing national-populist coalition) decided to erect a statue of Gabriele D'Annunzio, 100 years after he had occupied the nearby city of Fiume (now Rijeka) in Croatia. This commemoration led to a series of debates among historians, especially in Italy. Based on a critical discourse analysis and an interdiscursive approach to narratives produced by historians for colleagues and for the broader society, the current research investigates the use of cosmopolitanism in the field of history when in parallel a commemoration is coordinated by national-populist forces in a public space.